The effect of boron on oxide scale formation in a new polycrystalline superalloy. (15th January 2017) - Kontis, Paraskevas; Pedrazzini, Stella; Gong, Yilun; Bagot, Paul A.J.; Moody, Michael P.; Reed, Roger C.
Abstract: Boron addition to a new polycrystalline nickel-based superalloy promotes the formation of a hitherto unreported aluminoborate phase, in the scale produced by oxidation in air at 900 °C for ~ 10, 000 h. Atom probe tomography provides unambiguous confirmation of this. The ramifications of its formation are discussed. Graphical abstract: